2023
DOI: 10.1021/acs.est.3c02032
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Natural Phenolic Compounds in Polycyclic Aromatic Hydrocarbons Abiotic Attenuation at Soil–Air Interfaces through Oxidative Coupling Reactions

Abstract: Little information is available on the roles of natural phenolic compounds in polycyclic aromatic hydrocarbons (PAHs) attenuation at dry soil–air interfaces. The purpose of this study was to determine the roles of model phenolic constituents of soil organic matter (SOM) on the abiotic attenuation of PAHs. The phenolic compounds can significantly change the attenuation rates of PAHs, among which hydroquinone was the most effective in promoting anthracene and benzo[a]anthracene attenuation. Product identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Significant four characteristic peaks of intensity 1:2:2:1 and three characteristic signals of intensity 1:1:1 were detected in the system where PSMPs were coincubated with FA <1kDa and HA <1kDa under UV illumination, which were stronger other MW DOM (Figure S10). In simulated sewage treatment processes (40−48 μm bulk white PSMPs) and natural vitamin C-induced processes (1 μm globular white PSMPs), similar signals can be observed, but with a weaker overall intensity, 16,45 possibly predicting a higher environmental activity and ROS-generating capacity of lower MW DOM. In addition, Fe 2+ was not detected within the detection limit of phenanthroline-UV spectrophotometry in different MW DOM, which directly refuted our earlier hypothesis and confirmed that signals in the EPR were not derived from the Fenton reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Significant four characteristic peaks of intensity 1:2:2:1 and three characteristic signals of intensity 1:1:1 were detected in the system where PSMPs were coincubated with FA <1kDa and HA <1kDa under UV illumination, which were stronger other MW DOM (Figure S10). In simulated sewage treatment processes (40−48 μm bulk white PSMPs) and natural vitamin C-induced processes (1 μm globular white PSMPs), similar signals can be observed, but with a weaker overall intensity, 16,45 possibly predicting a higher environmental activity and ROS-generating capacity of lower MW DOM. In addition, Fe 2+ was not detected within the detection limit of phenanthroline-UV spectrophotometry in different MW DOM, which directly refuted our earlier hypothesis and confirmed that signals in the EPR were not derived from the Fenton reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 61%
“…In addition, Fe 2+ was not detected within the detection limit of phenanthroline-UV spectrophotometry in different MW DOM, which directly refuted our earlier hypothesis and confirmed that signals in the EPR were not derived from the Fenton reaction. It has been suggested that even without UV irradiation, soil organic matter or biochar with condensed structures rich in phenol and quinone moieties are able to transfer electrons to oxidants (O 2 ), , resulting in the formation of some resonance-stabilized radicals, such as cyclopentadienyls, and phenoxyls that further induce continuous ROS production through redox cycling, ultimately oxidizing and even mineralizing organic pollutants. These mechanisms enabled the generation of ROS from DOM containing various chromophores (e.g., phenolic and quinone moieties) in dark reactions with PSMPs.…”
Section: Resultsmentioning
confidence: 99%
“…The cross-coupling process is common in the solid surface according to previous study . In this study, the 2-CP molecule was liable to be sorbed on the soil surface due to its lipophilicity (partition coefficient, log P = 2.18). , Afterward, the solid surface might result in the formation of 2-CP radical, which in turn interacted with soil substances to generate the cross-coupling product. , Besides, product analysis also showed the cross-coupling product of 2,4-DCP (Figure S6b,c), which might be because 2,4-DCP tends to accumulate on the soil solid (log P = 2.99) and has an aromatic structure. Thus, the cross-coupling process could be responsible for the similar transformation efficiency (14.1–17.1%) of alternating and control systems in the presence of 1,10-phenanthroline.…”
Section: Resultsmentioning
confidence: 63%
“…56 In this study, the 2-CP molecule was liable to be sorbed on the soil surface due to its lipophilicity (partition coefficient, log P = 2.18). 17,18 Afterward, the solid surface might result in the formation of 2-CP radical, which in turn interacted with soil substances to generate the cross-coupling product. 18,57 Besides, product analysis also showed the cross-coupling product of 2,4-DCP (Figure S6b,c), which might be because 2,4-DCP tends to accumulate on the soil solid (log P = 2.99) and has an aromatic structure.…”
Section: Environmentalmentioning
confidence: 99%
See 1 more Smart Citation